Problems in Predicting New Product Growth for Consumer Durables - Heeler, Roger M.; Hustad, Thomas P. (Management Science, 1980)
A popular model of new product diffusion is applied in an international setting. Several limitations on its use are noted: instability with limited data, environmental differences, and systematic under reporting of estimated time to attain peak level of first purchase sales.